2006
DOI: 10.1055/s-2006-923790
|View full text |Cite
|
Sign up to set email alerts
|

Amount and Intensity of Physical Activity, Fitness, and Serum Lipids in Pre-Menopausal Women

Abstract: The aim of the study was to determine the association between the amount and the intensity of physical activity (PA) and lipid profile and fitness in pre-menopausal women. A cross-sectional study was conducted, sampling was stratified according to two age groups and two levels of PA, as assessed by the Minnesota Leisure Time PA Questionnaire. Serum lipid profile and sex hormones were measured. The study included 403 women. Total energy expenditure on PA was directly associated with HDL-cholesterol and inversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
8
0
6
Order By: Relevance
“…Our results agree a previous study using the same recommendations, but although LTPA increased, overweight or obesity increased and physical fitness decreased [66]. Considering the second criterion (>300 MET·min/day) [46], there were 62.5% MetS active participants and 93.1% non-MetS active participants; however, our study reported higher percentage of active people among MetS participants than previous related studies [46,67].…”
Section: Discussionsupporting
confidence: 89%
“…Our results agree a previous study using the same recommendations, but although LTPA increased, overweight or obesity increased and physical fitness decreased [66]. Considering the second criterion (>300 MET·min/day) [46], there were 62.5% MetS active participants and 93.1% non-MetS active participants; however, our study reported higher percentage of active people among MetS participants than previous related studies [46,67].…”
Section: Discussionsupporting
confidence: 89%
“…PCOS, in turn, is associated with IR, hyperinsulinemia, and T2DM (3033). Hyperandrogenemic PCOS phenotypes have the greatest degree of IR and inflammation (34). The presence of ≥3 annual reports of menstrual cycles ≥42 days during ages 14–19 years should focus diagnostic attention on hyperandrogenemia, hyperinsulinemia, and PCOS (30, 31, 35), with a goal of exercise/diet (36) and insulin sensitizers (3032, 37) to reduce hyperinsulinemia and hyperandrogenemia, and with an ultimate goal of primary prevention of T2DM, coronary heart disease (1, 2), and morbid obesity, all of which are associated with PCOS in adult women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that a variety of personal characteristics and environmental factors influence the composition of plasma lipids and lipoproteins, including age, gender and the associated hormonal changes in women, genetics, BMI, body weight, body composition, alcohol consumption, smoking behaviour and medication use (1,(4)(5)(6)(7)(8)(9)(10) . In addition, it has been shown that physical activity can affect the plasma lipid profile.…”
mentioning
confidence: 99%